The effect of chronic nitric oxide inhibition on vascular reactivity and blood pressure in pregnant rats - Takiuti, Nilton Hideto; Carvalho, Maria Helena Cetelli; Kahhale, Soubhi; Nigro, Dorothy; Barbeiro, Hermes Vieira; Zugaib, Marcel (São Paulo Medical Journal, 1999)
CONTEXT: The exact mechanism involved in changes in blood pressure and peripheral vascular resistance during pregnancy is unknown. OBJECTIVE:To evaluate the importance of endothelium-derivated relaxing factor (EDRF) and its main component, nitric oxide, in blood pressure and vascular reactivity in pregnant rats. DESIGN: Clinical trial in experimentation animals. SETTING: University laboratory of Pharmacology. SAMPLE: Female Wistar rats with normal blood pressure, weight (152 to 227 grams) and age (90 to 116 days). INTERVENTION: The rats were divided in to four groups: pregnant rats treated with L-NAME (13 rats); pregnant control rats (8 rats); virgin rats treated with L-NAME (10 rats); virgin control rats (12 rats). The vascular preparations and caudal blood pressure were obtained at the end of pregnancy, or after the administration of L-NAME in virgin rats. MAIN MEASUREMENTS: The caudal blood pressure and the vascular response to acetylcholine in pre-contracted aortic rings, both with and without endothelium, and the effect of nitric oxide inhibition, Nw-L-nitro-arginine methyl-ester (L-NAME), in pregnant and virgin rats. The L-NAME was administered in the drinking water over a 10-day period. RESULTS: The blood pressure decreased in pregnancy. Aortic rings of pregnant rats were more sensitive to acetylcholine than those of virgin rats. After L-NAME treatment, the blood pressure increased and relaxation was blocked in both groups. The fetal-placental unit weight of the L-NAME group was lower than that of the control group. CONCLUSION: Acetylcholine-induced vasorelaxation sensitivity was greater in pregnant rats and that blood pressure increased after L-NAME administration while the acetylcholine-induced vasorelaxation response was blocked.